Effects of Seed bed, Cultivars and Seed rates on Yield and Quality of Onion Sets (Allium cepa L.) - Aisha, A. Mohammedali; Elsadig., E. E. Elshukry; Abdellatief, M. Alamin; Ayoub, Z. Elhag (Journal of Agronomy Research, 2022)
Field experiments were conducted during three successive winter seasons 2010/11, 2011/12 and 2012 /13, at Shambat Research Station Farm on clay loam soil pH 7.8, to study the effects of seed bed, cultivars and seed rates and their interactions on onion set yield and quality. Two seed bed (flat and ridge), two cultivars Kamleen and Baftaim (S) and three seed rates 4, 8, 12 g / m² (40, 80, 120 kg / ha) were tested. The experimental design used was 2*2*3 Factorial in spilt-split plot design with four replications. Yield was evaluated as set yield t / ha, whereas, quality was evaluated as percentage of large (2.9-2.0 cm) and medium (1.9-1.0 cm) set size according to diameter and average of single set weight (g). Cultivar Baftaim (S) gave the highest set yield t/ha and average of single set weight in the three seasons. The seed rate of 4 g/m² (40 kg / ha) resulted in highest average of single set weight and the highest number percentage of large set size. Increasing the seed rate increased set number and quality; the seed rate 12 g/m² (120 kg/ha) gave the highest percentage of medium set size.
Keywords: Seed bed; Cultivars; Seed rates; Yield; Onion Sets